MANAJEMEN BERBASIS KINERJA UNTUK MENGELOLA SISTEM PENDIDIKAN DI MADRASAH IBTIDAIYAH SWASTA NURUL FALAH CIPUTAT - Setya, Rakha Putra; Azzahra, Raden Adjeng Ayu Mutiara Herda; Kusumaningrum, Hesti (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2024)
Strategic management based on educational performance can be said to be a process of planning, measuring, assessing, and evaluating personnel performance to realize educational goals and optimize personnel's potential. The role of the head of MIS Nurul Falah is certainly required to be able to manage the education system in Madrasah properly. This study aims to determine how the strategy of the head of MIS Nurul Falah manages performance-based management of existing personnel. The research method used in this research is literature study research using books, scientific articles, and documents supported by descriptive qualitative research with interview and observation data analysis methods. The results of this study indicate that the madrasah head in managing performance-based management uses a system of recruitment, orientation, empowerment and organization, compensation, development and training, evaluation, and dismissal. Through this system, the madrasah head is objectively proven to be able to manage the existing education system in Madrasah properly, produce optimal education, and find the right solutions and work programs.